"It is a way of life": detecting Chinese students' wellbeing during the Spring Festival homecoming. Issue 5 (12th June 2020) - Zhao, Ying; Chen, Fangfang; Xu, Honggang
ABSTRACT: This paper follows the call for a "mobility turn" in the social sciences and attempts to understand the relationship between the annual Spring Festival homecoming and wellbeing by focusing on student mobility. Sixteen students are selected; their movements for two weeks around the Spring Festival are tracked, and their experiences are solicited in interviews. The relationship of interest is explored in three dimensions: physical movement, social connections and contextual shifts. The results show that students are eager to pursue an ideal home for their wellbeing but do not always obtain positive wellbeing. In reality, they face both physical and mental contradictions.